Prairie : a North American guide - Winckler, Suzanne, 1946- (Bur Oak guide., 2004)
Suzanne Winckler's goal is to encourage travelers to get off the highways, out of their cars, and onto North America's last remaining prairies. She makes this adventure as easy as possible by providing exact driving directions to the more than three hundred sites in her guide. She also includes information about size, management, phone numbers, and outstanding characteristics for every prairie site and provides readers with a thorough list of recommended readings and Web sites.